2020
DOI: 10.1038/s41598-020-75053-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization of two matrine derivatives and their cytotoxic effect on Sf9 cell of Spodoptera frugiperda

Abstract: The invasion of Spodoptera frugiperda has imposed a serious impact on global food security. Matrine is a botanical pesticide with a broad spectrum of insecticidal activity which was recommended for controlling Spodoptera frugiperda. In order to discover effective insecticide for Spodoptera frugiperda, two matrine derivatives modified with carbon disulfide and nitrogen-containing groups were systhesized. And their inhibition activities on Sf9 cell were evaluated. The structural configuration of compounds were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A content increase for 9 was observed from PE3-7, but no longer detected from PE9. This compound is vital due to its antimicrobial [ 55 , 58 ], antiparasitic [ 59 ], cytotoxic [ 60 ], anticarcinogenic [ 61 ], antiviral, [ 62 ] and antimalarial properties [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…A content increase for 9 was observed from PE3-7, but no longer detected from PE9. This compound is vital due to its antimicrobial [ 55 , 58 ], antiparasitic [ 59 ], cytotoxic [ 60 ], anticarcinogenic [ 61 ], antiviral, [ 62 ] and antimalarial properties [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this same sense, new compounds have been synthesized from active molecules of natural origin with insecticidal activity, such as matrine, a heterocyclic compound derived from quinolizidine isolated from the roots of Sophora flavescens (Aiton) and Sophora alopecuroides L. These molecules were introduced to groups of 1-pyrrolidinecarbodithioate and diethylcarbamodithioate to improve their activity through chemical synthesis, enhancing this activity at low concentrations; the structures of these new matrine derivatives are shown in Figure 4 [ 1 ].…”
Section: Chemical Insecticidesmentioning
confidence: 99%
“…Mortality and time of death were evaluated, and the authors concluded that halogenated flavones had insecticide activity. In this same sense, new compounds have been synthesized from active molecules of natural origin with insecticidal activity, such as matrine, a heterocyclic compound derived from quinolizidine isolated from the roots of Sophora flavescens (Aiton) and Sophora alopecuroides L. These molecules were introduced to groups of 1-pyrrolidinecarbodithioate In this same sense, new compounds have been synthesized from active molecules of natural origin with insecticidal activity, such as matrine, a heterocyclic compound derived from quinolizidine isolated from the roots of Sophora flavescens (Aiton) and Sophora alopecuroides L. These molecules were introduced to groups of 1-pyrrolidinecarbodithioate and diethylcarbamodithioate to improve their activity through chemical synthesis, enhancing this activity at low concentrations; the structures of these new matrine derivatives are shown in Figure 4 [1]. Other compounds tested are gamma-aminobutyric acid (GABA) antagonists, which resulted in an exciting drug target in lepidopteran and other plagues.…”
Section: Chemical Insecticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Lawson reagent to replace the oxygen atom on the carbonyl group of matrine with a sulfur atom and undergo a nucleophilic addition reaction with the active group at position C13, a series of thiomatrine derivatives were synthesized, which have antiliver fibrosis and antihepatitis activities [ 16 , 17 ]. Additionally, the introduction of nitrogen-containing and sulfur-containing derivatives synthesized at the C13 position of matrine has good insecticidal activity against Lipaphis erysimi , root knot nematode and Spodoptera frugiperda [ 18 , 19 , 20 ]. The derivative that was obtained by introducing dimethyl carbonate group condensed ester at the C14 position of matrine, and then reduced to alcohols and decarbonylated by lithium aluminum hydride has a significantly higher antitobacco mosaic virus and plant fungicidal activities than matrine [ 21 ].…”
Section: Introductionmentioning
confidence: 99%